Dinamika Psikologis dalam Proses Belajar Siswa SMP - Melanie Indah Nurwahid; Siti Latifah Mubasiroh (STIKes Ibnu Sina Ajibarang, 2025)
Students' learning processes are not only determined by cognitive abilities but are also greatly influenced by accompanying psychological aspects. At the junior high school (SMP) level, students are in the early adolescence phase, which is characterized by significant changes in emotions, motivation, and social needs. This condition makes psychological aspects a crucial factor in determining learning success. This study aims to examine the psychological dynamics that influence the learning process of junior high school students and their implications for the implementation of learning. The research method used is field research with a descriptive qualitative approach. The results show that learning motivation, emotional state, learning strategies, and social environmental support have interrelated roles in shaping students' learning experiences. Differences in students' psychological states contribute to variations in engagement and learning outcomes. Therefore, understanding students' psychological dynamics is crucial for teachers in designing effective, comfortable, and meaningful learning.